1990
DOI: 10.1002/j.1551-8833.1990.tb06921.x
|View full text |Cite
|
Sign up to set email alerts
|

Removing Radium by Adding Preformed Hydrous Manganese Oxides

Abstract: Batch and pilot‐scale studies demonstrated that the addition of preformed hydrous manganese oxides (HMOs) appears to be a feasible approach to removing radium from drinking water. Major advantages of this process include use of existing treatment facilities and simplicity of operation. Furthermore, no irreversible effects are expected if the HMOs are under‐ or overdosed, other than possible inadequate radium removal or shortened filter runs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The authors observed that the Pb adsorption capacity of MnO 2 exceeded that of its Fe‐oxide counterpart by an order of magnitude on a molar basis. Other researchers (Valentine & Stearns, 1994; Valentine et al, 1990) reported even more dramatic differences when assessing Ra removal via adsorption to preformed Fe and Mn oxides. They observed Ra sorption densities of 20,000–40,000 pCi/g (Ra‐to‐Mn ratio) onto hydrous Mn oxides (HMOs) when equilibrated to 5 pCi/L of Ra.…”
Section: Accumulation Sinksmentioning
confidence: 97%
See 1 more Smart Citation
“…The authors observed that the Pb adsorption capacity of MnO 2 exceeded that of its Fe‐oxide counterpart by an order of magnitude on a molar basis. Other researchers (Valentine & Stearns, 1994; Valentine et al, 1990) reported even more dramatic differences when assessing Ra removal via adsorption to preformed Fe and Mn oxides. They observed Ra sorption densities of 20,000–40,000 pCi/g (Ra‐to‐Mn ratio) onto hydrous Mn oxides (HMOs) when equilibrated to 5 pCi/L of Ra.…”
Section: Accumulation Sinksmentioning
confidence: 97%
“…Contaminant concentrations. The adsorption capacity ( q i,j,k ) of several contaminant–substrate pairings has been shown to be well‐represented by various isotherm distribution models (e.g., Freundlich, Langmuir) within certain pH ranges (Amy et al, 2005; McNeill & Edwards, 1997; Valentine & Stearns, 1994; Valentine et al, 1990). Although the shape of the adsorption capacity profiles differ between these models, in each case q i,j,k increases in a positive manner to C i .…”
Section: Water Chemistrymentioning
confidence: 99%
“…The 226 Ra was removed most efficiently with the manganese greensand filtration equipment (98%) with removal that is based on the use of potassium permanganate. Manganese dioxide forms a fresh coating on the greensand granulates and acts as an efficient adsorbent (Qureshi & Nelson, 2003; Valentine et al, 1990). Strong acid cation resins, which are normally used to remove Fe, Mn, and hardness from water, have been observed to remove more than 80% of 226 Ra (Vesterbacka et al, 2003; Clifford, 1990).…”
Section: Removal Efficiencymentioning
confidence: 99%
“…Iron oxides, which ordinarily occur in water treatment plants and distribution systems, selectively scavenge other elements primarily by adsorption or coprecipitation and may bind radium.10 In addition, radium can adsorb and/or coprecipitate to various substances, including iron and manganese oxides. [11][12][13][14] To examine whether the pipe scale contained 226Ra, we subjected the pipe scale samples to gamma analyses. HpGe detector gamma analyses of scale fragments identified several members of the uranium-238 (238U) decay chain, including 10 Bq/g-l of 226Ra and 5 Bq/g-I of 222Rn progeny.…”
Section: Introductionmentioning
confidence: 99%